الإستراتيجيات البديلة للإقتصاد الجزائري في ظل تقلبات لأسعار النفط للفترة 2000إلى 2016 - zouari ferhat, slimane (Finance and Business Economies Review, 2018)
This study is intended to address the current situation of the Algerian economy, which is suffering from the current oil crisis and its consequences as a result of the decline in revenues of the oil sector, which is considered the main sector based on the national economy. The first topic tackles the development of oil prices during the period (2000 to 2016). The second axis deals with the repercussions of oil prices on the Algerian economy for the period (2000 to 2016), and in The third axis is exposed to the expectations of the growth of the Algerian economy and economic reforms in light of the current oil crisis, and the fourth axis presents the proposed strategies for the national economy in the face of oil price shocks